¿Qué se aprende al empezar el trabajo y cómo? - Claire Tourmen; Annie Leroux; Sylvie Beney (Universidade do Porto, 2014)
Learning in the workplace is frequently considered a long process involving in-depth, diversified and repeated experience. However, the issue of how long that learning takes is still undetermined. Our goal was to explore what is learned (and how) during the first moments of work, the role of observation and the cultural dimension of the first learning experiences in the workplace. Based on a theoretical and methodological framework of vocational didactics inspired by work psychology and ergonomics, and complemented by a cultural psychology framework, we analyzed the work activity of social workers within two organizations, as well as the work activity of six experienced professionals and three first year interns. Our results show that some learning experiences take place in the first few moments of work. Some refer to the "cultural" dimensions of the workplace environment, which lead us to suggest the concept of "scene" in analyzing the first learning experiences in the workplace. their health and safety at work than perceived. Health damage was more frequent for hairdressing students. There were also gender approaches on health and safety at work. The discussion focuses on research methods and approaches, HSW approaches, interventions resulting from the research and elements in need of further development.